2002
DOI: 10.2176/nmc.42.259
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Spindle Cell Hemangioendothelioma of the Thoracic Spinal Cord

Abstract: A 28-year-old Malay man presented with progressive paraparesis over a period of 6 months. Magnetic resonance imaging of the spine revealed a thoracic intramedullary spinal cord tumor at the T-7 level with homogeneous enhancement following intravenous gadolinium administration. Laminectomy and partial decompression of the tumor was performed. Histological examination of the tumor revealed features of spindle cell hemangioendothelioma. The patient was managed with limited field radiotherapy followed by systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…A recent report by Roncaroli et al [6] suggested observation alone after surgery without adjuvant therapy, however, the follow-up period of 14 months in the reported case was comparatively short. The present case is similar to that reported by Abdullah et al [11] where postoperative limited fi eld radiation was given although there was no interferon therapy offered to our patient after radiation. Similar to that report, our patient has no evidence of progression of disease at 48 months' follow-up.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A recent report by Roncaroli et al [6] suggested observation alone after surgery without adjuvant therapy, however, the follow-up period of 14 months in the reported case was comparatively short. The present case is similar to that reported by Abdullah et al [11] where postoperative limited fi eld radiation was given although there was no interferon therapy offered to our patient after radiation. Similar to that report, our patient has no evidence of progression of disease at 48 months' follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Previous case reports involve tumor in the intradural and extramedullary sites [5] . Apart from two reports [6,11] , a literature review has failed to identify reports on primary spinal HE with intramedullary or partially intramedullary involvement as in the current case report. Secondly, postoperative radiotherapy was offered to the patient rather than observation.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…These vascular lesions most often present as solitary or multiple dermal or subcutaneous masses. SCH has been reported to occur in viscera such as the pancreas and spleen [11,36], as well as the spinal cord [1,26]. Osseous involvement has only been reported in three other patients [5,34,37], and two of these involved the hand.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 Contrary to other subtypes (that is, epithelioid), 10,12,[14][15][16]19,27,28 spindle cell hemangioendothelioma exhibits an acral predisposition, 11,12,14 with sporadic reports of these tumors in the oral cavity, 24 brain, 7 and thoracic spine. 1,22 We present the first known case of a spindle cell hemangioendothelioma involving the sacrum.…”
mentioning
confidence: 99%